Proposed Digital Marketing Strategy for Pempek Emak Seroja Restaurant (The Indonesian Journal of Business Administration, 2021)
Pempek Emak Seroja is a restaurant that sells pempek as its trademark which was founded by Agni Hendrawati Tuah in 2018, located on Jalan Taman Ratu Kemuning Blok D11 no. 26C, Duri Kepa - West Jakarta, Indonesia. Their restaurant is open daily from 10am - 7pm. Over time, sales at the Pempek Emak Seroja restaurant were unstable every month. This research will provide marketing strategy solutions to solve the problems faced by Pempek Emak Seroja restaurant in an effort to determine the root cause of Pempek Emak Seroja in brand awareness problem and to find the marketing strategy to improve the brand awareness of Pempek Emak Seroja.This research project is carried out using a qualitative method with a combination of primary and secondary data. Primary data obtained came from interviews with restaurant managers, employees and consumers. The author also uses secondary data obtained from several sources such as websites, articles, etc. to support this research. This research begins with the interpretation of business problems, followed by analyzing marketing problems which are divided into two parts: Internal and External Analysis. Internal analysis was carried out using the STP analysis method, marketing mix, company resources. External analysis will be carried out using PESTEL and Porter's 5 forces, competitor and consumer analysis.Based on the results of the overall analysis, this study produces a SWOT matrix, and identifies the root of the problem. There are three reasons for Pempek Emak Seroja's problems, namely: not optimal use of the digital platform, lack of marketing content and no creative content. After knowing the cause of the problem, several alternative solutions were formulated in the TOWS matrix. Then the alternative solutions are matched with the root of the problem to produce a strategy. As a result, the authors identified that digital marketing is an important key to the problems faced by Pempek Emak Seroja. This study proposes five strategies to improve brand awareness of Pempek Emak Seroja restaurant. Keywords: Business strategy, Indonesian Food, Decreased sales, Digital marketing, Marketing mix.